CC-003 Abnormal liver function tests and hepatomegaly in a diabetic patient: an under-recognised diagnosis. (23rd September 2015) - Hamid, R; MacGilchrist, A; Belllamy, C
Abstract : Introduction: We report the case of a 29-year-old type 1 diabetic who presented with abnormal liver function tests (LFTs) and RUQ discomfort. At that time she was 7 months post-partum. Physical examination revealed 2 cm tender hepatomegaly. Initial investigations showed the following. (a) Blood tests: bilrubin 5; ALT 256; ALP 137 and GGT 112. A liver screen was essentially negative. (b) Abdominal ultrasound: diffusely enlarged liver. No ascites and vasculature normal. (c) Liver biopsy: reported as showing "diffuse microvesicular change but with no inflammation and mild perisinusoidal fibrosis". A diagnosis of severe microvesicular steatosis of unknown aetiology was made. Methods: The patients symptoms of abdominal discomfort gradually settled. Her LFTs also completely settled back to normal in January 2004 and it was felt that whatever the insult was to her liver a few months earlier, it was now settling. The patient continued follow-up at the liver clinic with her LFTs fluctuating but occasionally settling completely back to normal. Results: The patient was readmitted with complaints of severe abdominal chest pain and was admitted for further investigation. Physical examination revealed marked abdominal distension with the clinical impression of ascites. Blood tests showed deterioration in her LFTs. An urgent CT was undertaken. The CT scan showed a markedly enlarged liver which was not particularly fatty on imaging. We proceeded to a repeat liver biopsy. Hepatic glycogenopathy (glycogenosis) was diagnosed. The biopsy was compared to the previous biopsy. Similar changes were in fact noted in the initial biopsy but, with an overlay of microvesicular and some macrovesicular steatosis, along with a poor appreciation of the disease at that time, led to glycogenosis being overlooked. Conclusion: This case highlights the importance of considering hepatic glycogenosis in patients with diabetes, hepatomegaly and abnormal LFTs. Hepatic enlargement in diabetes is usually the result of either glycogenosis or non-alcoholic steatohepatitis (NASH). Glycogenosis is the hepatic response to poor glycaemic control in children, adolescence and adults with Type 1 diabetes, while NASH is the more likely diagnosis in adults with type 2 diabetes. Hepatic glycogenosis has been reported previously but remains under-recognised. As mentioned, it is associated with poor glycaemic control (hyperglycaemia and intermittent insulin administration) but is readily treatable by improvement of glycaemic control. It is a benign disease with little chance of progression to fibrosis. Liver biopsy is definitive in the diagnosis of hepatic glycogenosis. An excess of glycogen in the nucleus of the hepatocytes is seen, which are pale and swollen, with peripherally displaced organelles. Steatosis is absent in up to 90% of cases and helps distinguish this condition from NASH. However, our case illustrates that glycogenosis can easily be overlooked probably due to an under appreciation of the condition.